Diagnostic test accuracy of self‐reported screening instruments in identifying frailty in community‐dwelling older people: A systematic review. Issue 1 (14th November 2019) - Ambagtsheer, Rachel C; Thompson, Mark Q; Archibald, Mandy M; Casey, Mavourneen G; Schultz, Timothy J
Abstract : Against a backdrop of aging populations worldwide, it has become increasingly important to identify frailty screening instruments suitable for community settings. Self‐reported and/or administered instruments might offer significant simplicity and efficiency advantages over clinician‐administered instruments, but their comparative diagnostic test accuracy has yet to be systematically examined. The aim of this systematic review was to determine the diagnostic test accuracy of self‐reported and/or self‐administered frailty screening instruments against two widely accepted frailty reference standards (the frailty phenotype and the Frailty Index) within community‐dwelling older adult populations. We carried out a systematic search of the Embase, CINAHL, MEDLINE, PubMed, Web of Science, PEDro, PsycINFO, ProQuest Dissertations, Open Grey and GreyLit databases up to April 2017 (with an updated search carried out over May–July 2018) to identify studies reporting comparison of self‐reported and/or self‐administered frailty screening instruments against an appropriate reference standard, with a minimum sensitivity threshold of 80% and specificity threshold of 60%. We identified 24 studies that met our selection criteria. Four self‐reported screening instruments across three studies met minimum sensitivity and specificity thresholds. However, in most cases, study design considerations limited the reliability and generalizability of the results. Additionally, meta‐analysis was not carried out, because no more than three studies were available for any of the unique combinations of index tests and reference standards. Although the present study has shown that a number of self‐reported frailty screening instruments reported sensitivity and specificity within a desirable range for community application, additional diagnostic test accuracy studies are required. Geriatr Gerontol Int 2020; 20: 14–24 .